2022
DOI: 10.1172/jci.insight.157963
|View full text |Cite
|
Sign up to set email alerts
|

Binding and neutralizing antibody responses to SARS-CoV-2 in very young children exceed those in adults

Abstract: is detailed in Supplemental Acknowledgments. METHODS.We compared receptor binding domain-binding antibody (RBDAb) titers and SARS-CoV-2-neutralizing antibody titers, measured by pseudovirus-neutralizing antibody assay in serum specimens obtained from children aged 0-4 years and 5-17 years and in adults aged 18-62 years at the time of enrollment in a prospective longitudinal household study of SARS-CoV-2 infection.RESULTS. Among 56 seropositive participants at enrollment, children aged 0-4 years had more than 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Consistently, a very recent study reported that young children aged 0-4 years generally develop significantly higher titers of neutralizing antibody than adults. This study also documented a stepwise downward progression in binding-to-neutralizing (B/ N) antibody titer ratio with age: children aged 0-4 years had the highest ratio of B/N antibody, children aged 5-17 years had an intermediate level, and adults had the lowest (21). So far, the exact mechanisms underlying the different SARS-CoV-2 antibody responses based on age remain unclear.…”
Section: Discussionmentioning
confidence: 62%
“…Consistently, a very recent study reported that young children aged 0-4 years generally develop significantly higher titers of neutralizing antibody than adults. This study also documented a stepwise downward progression in binding-to-neutralizing (B/ N) antibody titer ratio with age: children aged 0-4 years had the highest ratio of B/N antibody, children aged 5-17 years had an intermediate level, and adults had the lowest (21). So far, the exact mechanisms underlying the different SARS-CoV-2 antibody responses based on age remain unclear.…”
Section: Discussionmentioning
confidence: 62%
“…Concerning the high titers of anti-S among children in our study, similar results were noted by Garrido et al, who reported higher anti-RBD and neutralizing antibodies in children than in adults, up to 4 months post-COVID-19 infection [ 34 ]. In addition to cross-reactivity with other coronaviruses, Karron et al, explained the higher SARS-CoV-2 seropositivity among children by their exaggerated tenfold higher RBD antibody titers than adults, while adults had a higher neutralizing ability than children [ 35 ]. Children were reported to have more durable, yet immature RBD-specific antibody responses [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observation that IgG titers against nucleocapsid and SH-H were the same in infants and adults in this study suggests that the stronger responses in infants to other domains cannot simply be explained by higher overall B lymphocyte levels reported in infants versus adults (O’Gorman et al, 1998). Previous studies have detected lower (Hachim et al, 2022), higher (Karron et al, 2022; Yang et al, 2021), or equivalent (Goenka et al, 2021; Weisberg et al, 2021) levels of antibody binding to Spike or its subdomains in pediatric cohorts compared to adults. One possible reason for this variation is the inclusion of children who span a wide age range in prior studies, whereas this study specifically focused on infants (under 19 months of age), with samples collected within a single cohort study (Begnel et al, 2023).…”
Section: Discussionmentioning
confidence: 92%
“…While prior studies have assessed neutralization capacity in cohorts that include older children (Dowell et al, 2022; Karron et al, 2022; Weisberg et al, 2021; Yang et al, 2021), few studies have assessed SARS-CoV-2 antibody function (Goenka et al, 2021) in infants early in life or directly compared antibody responses in infants and adults. Though antibody neutralization of SARS-CoV-2 remains a key component of protective and therapeutic immunity, there is increasing evidence for the importance of non-neutralizing antibody effector functions, such as Fc receptor-mediated antibody-dependent cellular cytotoxicity (ADCC) in protection against SARS-CoV-2 (Beaudoin-Bussieres et al, 2022; Di Vito et al, 2022; Pierce et al, 2020; Rostad et al, 2022; Tauzin et al, 2021; Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%